2016
DOI: 10.5812/aapm.31046
|View full text |Cite
|
Sign up to set email alerts
|

Skin Temperature Over the Carotid Artery, an Accurate Non-invasive Estimation of Near Core Temperature

Abstract: Background:During anesthesia, continuous body temperature monitoring is essential, especially in children. Anesthesia can increase the risk of loss of body temperature by three to four times. Hypothermia in children results in increased morbidity and mortality. Since the measurement points of the core body temperature are not easily accessible, near core sites, like rectum, are used.Objectives:The purpose of this study was to measure skin temperature over the carotid artery and compare it with the rectum tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Similar studies have been conducted in infants and children where the skin temperature over carotid is comparable with the rectal temperature. 7 In another study, the author concluded that skin temperature over carotid is comparable with nasopharyngeal temperature with correction factor of +0.52° C. 6 Our results are in agreement with the study conducted by Venkatesh et al 8 Since the transcutaneous carotid temperature monitoring is a non-invasive technique with acceptable accuracy in core temperature monitoring this can routinely be used. The problems related to invasive techniques e.g., trauma or cross infection can easily be avoided.…”
Section: Discussionsupporting
confidence: 87%
“…Similar studies have been conducted in infants and children where the skin temperature over carotid is comparable with the rectal temperature. 7 In another study, the author concluded that skin temperature over carotid is comparable with nasopharyngeal temperature with correction factor of +0.52° C. 6 Our results are in agreement with the study conducted by Venkatesh et al 8 Since the transcutaneous carotid temperature monitoring is a non-invasive technique with acceptable accuracy in core temperature monitoring this can routinely be used. The problems related to invasive techniques e.g., trauma or cross infection can easily be avoided.…”
Section: Discussionsupporting
confidence: 87%
“…This was the first study to compare neck IFR and rectal temperatures. [ 20 ] IFR measures on the lateral side of neck the most reliable in children aged 2 to 6 years. However, the study methodology differed from ours; the cited authors used logistic regression analyses to evaluate multivariable data.…”
Section: Discussionmentioning
confidence: 99%
“…Other skin sites have also been reported as potentially promising in the prediction of deep body temperature, such as the skin above the carotid artery (Jay et al 2013;Imani et al 2016). These sites may not be optimal for mass screening, but could provide confirmatory data.…”
Section: Possible Solutions?mentioning
confidence: 99%